1988
DOI: 10.1007/bf00333397
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Tn5 derivative encoding bioluminescence and its introduction in Pseudomonas, Agrobacterium and Rhizobium

Abstract: A simple method based upon the use of a Tn5 derivative, Tn5-Lux, has been devised for the introduction and stable expression of the character of bioluminescence in a variety of gram-negative bacteria. In Tn5-Lux, the luxAB genes of Vibrio harveyi encoding luciferase are inserted on a SalI--BglII fragment between the kanamycin resistance (Kmr) gene and the right insertion sequence. The transposon derivative was placed on a transposition suicide vehicle by in situ recombination with the Tn5 suicide vector pGS9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…To study the patterns of microbial plant root colonization, different tools such as microscopy (Chin-A-Woeng et al 1997;Rovira et al 1974), microscopy combined with the use of marked strains (Bloemberg et al 1997), or strains equipped with reporter genes (Beauchamp et al 1993;Boivin et al 1988;de Weger et al 1991;Kloepper and Beauchamp 1992) can be used. During in vitro studies, it was shown that, upon inoculation of seed or seedlings, cells of Pseudomonas mainly appear as microcolonies along the junctions of epidermal plant cells where nutrients are exuded Chin-A-Woeng et al 1997).…”
Section: Rhizoremediationmentioning
confidence: 99%
“…To study the patterns of microbial plant root colonization, different tools such as microscopy (Chin-A-Woeng et al 1997;Rovira et al 1974), microscopy combined with the use of marked strains (Bloemberg et al 1997), or strains equipped with reporter genes (Beauchamp et al 1993;Boivin et al 1988;de Weger et al 1991;Kloepper and Beauchamp 1992) can be used. During in vitro studies, it was shown that, upon inoculation of seed or seedlings, cells of Pseudomonas mainly appear as microcolonies along the junctions of epidermal plant cells where nutrients are exuded Chin-A-Woeng et al 1997).…”
Section: Rhizoremediationmentioning
confidence: 99%
“…To complete the series, mini-Tn5xylE and mini-TnSluxAB elements were developed also. These produce type I fusions to catechol 2,3-dioxygenase of Pseudomonas putida (34) and to the luciferase genes of Vibrio harveyi, respectively (3,7,17). These two reporter genes are convenient alternatives to lacZ in a variety of applications (5).…”
mentioning
confidence: 99%
“…Two advantages of this approach, beyond the reduction in size of the transposon insert, are that it prevents further transposition and that it permits additional rounds of mini transposon mutagenesis because no immunity protein is present in the cell [11]. Whereas TnphoA and Tnlacz can be used to explore membrane protein topology, TnluxAB encodes bioluminescence and can be used to visualize bacterial presence for example in an inoculated Rhizobial strain [12].…”
Section: Discussionmentioning
confidence: 99%